Operationalising digital soil mapping – Lessons from Australia - Kidd, Darren; Searle, Ross; Grundy, Mike; McBratney, Alex; Robinson, Nathan; O'Brien, Lauren; Zund, Peter; Arrouays, Dominique; Thomas, Mark; Padarian, José; Jones, Edward; Bennett, John McLean; et al. (Geoderma Regional, 2020)
Australia has advanced the science and application of Digital Soil Mapping (DSM). Over the past decade, DSM in Australia has evolved from being purely research focused to become ‘operational’, where it is embedded into many soil-agency land resource assessment programs around the country. This has resulted from a series of ‘drivers’, such as an increased need for better quality and more complete soil information, and ‘enablers’, such as existing soil information systems, covariate development, serendipitous project funding, collaborations, and Australian DSM ‘champions’. However, these accomplishments were not met without some barriers along the way, such as a need to demonstrate and prove the science to the soil science community, and rapidly enable the various soil agencies' capacity to implement DSM. The long history of soil mapping in Australia has influenced the evolution and culmination of the operational DSM procedures, products and infrastructure in widespread use today, which is highlighted by several recent and significant Australian operational DSM case-studies at various extents. A set of operational DSM ‘workflows’ and ‘lessons learnt’ have also emerged from Australian DSM applications, which may provide some useful information and templates for other countries hoping to fast-track their own operational DSM capacity. However, some persistent themes were identified, such as applicable scale, and communicating uncertainty and map quality to end-users, which will need further development to progress operational DSM. •Australia has a long history in the development of Digital Soil Mapping (DSM).•Australian DSM has become operational due to a history of drivers and enablers.•Operational protocols and lessons learnt have emerged from exemplar DSM products.•Operational DSM has been empowered by an Australian ‘Community of Practice’.